Influence of growth temperature and miscut angle of m-plane sapphire substrate on the semi-polar (11–22) AlN film grown by HVPE - Maosong, Sun; Ting, Liu; Yong, Lu; Shuxin, Tan; Xu, Li; Jicai, Zhang; Wenhong, Sun (Frontiers in Physics, 2022)
The high-quality semi-polar (11-22) AlN thin films were grown on m-plane sapphire substrates by hydride vapor phase epitaxy (HVPE). The surface morphology and crystalline quality of the AlN film were greatly influenced by the growth temperature and the substrate miscut angle. As the temperature increased, the grain size on the surface increased and the grain density decreased. In addition, the higher growth temperature also resulted in smaller values of the full width at half maximum (FWHM) of X-ray rocking curves (XRC) when temperature was more than 1460 °C. At high temperature of 1530 °C, the introduction of 1°-off miscut angle to the substrate resulted in smooth surface, low density of stacking faults and low FWHM of XRC. The misfit dislocation density was calculated from the tilt angle of epilayer measured by X-ray reciprocal space mappings along [-1-123] AlN. The misfit dislocation density of the sample grown on 1°-off substrates was 6.7 × 105 cm-2. The improvement of crystal quality is believed to be due to the enhancement of adatom mobility at higher temperatures and also the appropriate miscut variation.